2006
DOI: 10.1038/sj.bjc.6603511
|View full text |Cite
|
Sign up to set email alerts
|

Complementary effects of HDAC inhibitor 4-PB on gap junction communication and cellular export mechanisms support restoration of chemosensitivity of PDAC cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a fatal disease and one of the cancer entities with the lowest life expectancy. Beside surgical therapy, no effective therapeutic options are available yet. Here, we show that 4-phenylbutyrate (4-PB), a known and welltolerable inhibitor of histone deacetylases (HDAC), induces up to 70% apoptosis in all cell lines tested (Panc 1, T4M-4, COLO 357, BxPc3). In contrast, it leads to cell cycle arrest in only half of the cell lines tested. This drug increases gap junction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 43 publications
6
28
0
Order By: Relevance
“…Interestingly, TSA also downregulated this ABCC1 gene expression in H69VP drug-resistant cells (data not shown). Thus, our results support the idea that HDAC inhibitors could modulate MDR through simultaneous inhibition of different ABC transporters as recently suggested for 4-phenylbutyrate (Ammerpohl et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, TSA also downregulated this ABCC1 gene expression in H69VP drug-resistant cells (data not shown). Thus, our results support the idea that HDAC inhibitors could modulate MDR through simultaneous inhibition of different ABC transporters as recently suggested for 4-phenylbutyrate (Ammerpohl et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…In line with these data there have been reported observations showing that the histone deacetylases inhibitor 4-phenylbutyrate, an agent known to increase gap junction communication capacity, enhances gemcitabinemediated apoptosis in pancreatic tumor cells (36). In this sense, another pharmacologic agent that is known to enhance GJIC and has proved benefits to gemcitabine treatment is tamoxifen.…”
Section: Discussionsupporting
confidence: 62%
“…Efficacy of 4-PBA in alleviation of ER stress has been demonstrated in a variety of tissues in earlier studies, including ours (13,17,29). On the other hand, 4-PBA is also known to suppress histone deacetylase (HDAC) activity (1,16). Recently, Zhao et al (36) found that HDAC activity in lung tissue was significantly increased in patients with end-stage idiopathic PAH and in a rat model of hypoxiainduced PAH.…”
Section: Discussionmentioning
confidence: 95%